OGC O08 Endoscopic surveillance alone is feasible and safe in type I gastric neuroendocrine neoplasms less than 10mm in diameter. (7th December 2022) - Exarchou, Klaire; Hu, Haiyi; Stephens, Nathan A; Moore, Andrew R; Kelly, Mark; Lamarca, Angela; Mansoor, Wasat; Hubner, Richard; McNamara, Mairead G; Smart, Howard; Howes, Nathan R; Valle, Juan W; et al.
Abstract: Background: Type I gastric neuroendocrine neoplasms (g-NENs) have a low risk of metastasis and a generally favourable prognosis. Patients with small type I g-NENs (≤10mm) frequently require no treatment, whereas those with larger polyps usually undergo resection. We evaluated the safety and outcomes of endoscopic surveillance after no initial treatment in selected patients with type I g-NENs. Methods: Retrospective analysis of type I g-NEN patients across two European Neuroendocrine Tumour Society Centers of Excellence 2003–2019. Results: Following initial assessment, 87 of 115 patients with type I g-NEN (75 with polyps ≤10mm) received no initial treatment and underwent endoscopic surveillance. 79/87 (91%) demonstrated no clinically meaningful change in tumour size or grade over a median 62 month follow up. Only two patients developed NEN progression that required a change in management and two other patients developed gastric adenocarcinoma/high grade dysplasia; all four initially had ≥11mm g-NENs. Conclusions: Patients with ≤10mm type I g-NENs were unlikely to develop clinically significant tumour progression and in most cases, resection was not needed. The endoscopic surveillance interval could therefore potentially be safely increased to every 2–3 years in such patients. However, lifelong surveillance is still advocated due to the additional risk of developing gastric adenocarcinoma.